Elevated serum visfatin/nicotinamide phosphoribosyl-transferase levels are associated with risk of postmenopausal breast cancer independently from adiponectin, leptin, and anthropometric and metabolic parameters. - Dalamaga, Maria; Karmaniolas, Konstantinos; Papadavid, Evangelia; Pelekanos, Nicolaos; Sotiropoulos, George; Lekka, Antigoni (Menopause, 2011)
OBJECTIVE: Obesity has been implicated in the etiology of postmenopausal breast cancer (PBC). We hypothesized that altered secretion of visfatin may underlie this association. We thus investigated the association of serum visfatin with PBC risk, taking into account known risk factors including adipokines and anthropometric and metabolic parameters. METHODS: In a case-control study, we studied 102 postmenopausal women with pathologically confirmed, incident invasive breast cancer and 102 control women matched on age and time of diagnosis between 2003 and 2010 at Army Share Fund Hospital, Veterans' Hospital (NIMTS). Levels of serum visfatin, adiponectin, leptin, metabolic parameters, carcinoembryonic antigen, and CA 15-3 were determined. RESULTS: The mean serum visfatin level was significantly higher in case than in control participants (P < 0.001). Women in the highest quartile of visfatin concentration presented significantly higher odds for PBC, adjusting for age, date of diagnosis, education, body mass index, waist circumference, years with menstruation, parity/age at first full-term pregnancy, breast-feeding, family history of cancer, use of exogenous hormones, alcohol consumption, smoking status, homeostasis model assessment score, and serum leptin and adiponectin concentrations (odds ratio, 7.93; 95% CI, 2.52-24.9). In case participants, the visfatin level correlated significantly with the tumor marker CA 15-3 (P = 0.03) but not with metabolic and anthropometric variables (P > 0.05). CONCLUSIONS: Further prospective studies are needed to determine whether an elevated serum visfatin level is implicated in the etiopathogenesis of PBC or reflects changes during PBC progression and could therefore be used as a biomarker for PBC.
Keywords: Adiponectin; Aged; Aged, 80 and over; Biomarkers; Breast Neoplasms; Carcinoembryonic antigen; Case-Control Studies; Cytokines; Female; Humans; Leptin; Logistic Models; Middle Aged; Mucin-1; Nicotinamide Phosphoribosyltransferase; Obesity; Odds Ratio; POSTMENOPAUSE; Risk